“It’s not just a picture book!”: Expanding ideas of multiliteracies through the creation and assessment of a multimodal assignment - Ahn, Claire; Evans, Rebecca S.; Chin, Jane (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2026)
Grounded in a multiliteracies framework, this article interweaves the authors’ experiences through narrative inquiry, exploring the integrating of multimodal texts and multimodal approaches of assessment within their practice. The article is organized as a conversation between two educators and a former student, and is centred around a multimodal assignment in a secondary English teacher education class that asked teacher candidates to create a digital picture book and use video annotation in peer assessment. Our shared conversation highlights the importance of multimodal texts such as sophisticated picture books in the secondary English classrooms, as well as thinking about alternative multimodal approaches to assessment.